ACHIEVING HIGH PRODUCTIVITY AND QUALITY BY WORKING AS A TEAM-WORK IN THE ORGANIZATIONS - Jabbar, Ali Abdulridha (International Journal of Research -GRANTHAALAYAH, 2017)
Increasing productivity is one of the most critical goals in an organization. Also the quality of the markets is an important target that many experienced managers who emphasize the merits of "good teamwork" have numerous behavioral requirements in mind. Their claims remain rather vague and meaningless, however, as long as the essence of a team, the quality of its collaborative working, is neither precisely defined nor validly and reliably measured and that explain which aspects of teamwork are relevant to team performance and then testing these propositions to make distinctions that are useful for particular purposes. This paper will explain mission and objectives of organizations with the strategies of the organizations and the external and internal analysis which include Strengths, Weaknesses, Opportunities and Threats factors. The objectives are developed in line with the management, communication skills, boosting employees’ morale, strategic planning and achieving high productivity and quality are what the members of the team should know. To work as a team, the organization must teach its employees’ on the process that could lead towards achieving their objectives. These could be in terms of how they should prepare, how to temper emotion towards achieving the organization objectives.